LOKAKARYA DAN PELATIHAN TEKNOLOGI MEDIA GEREJA DI MEDIA SEVEN PRODUCTION - Robertus Suryadi; Eko Agus Setiawan; Stefan Rumaijuk (JURNAL BEATITUDES, 2022)
The church needs to make some efforts to help the church where we belong, especially in terms of evangelizing to all people of this age. That's why this media technology as a means for me to realize this longing. We often find in today's churches, there is still a lot of communication to the congregation that must be done digitally or through technology media, but it is still done conventionally. In addition, especially so many churches are still not "literate" technology. This we can see not only churches with congregations of less than a hundred people, but also churches that have congregations of more than a thousand people. Where they do not have social media accounts, such as Facebook, Instagram, Youtube Channel, Apps, and even Website. Media Seven Production provides opportunities to develop existing Christian media services. In order to know more about the facilities and infrastructure of the media technology itself. They can also learn and even become direct executors in the pre-production to post-production processes. So that the congregation can enjoy the content produced by the technology media itself. Not only as a medium that can be seen and felt, but also can trigger the acceleration of the spiritual growth of the congregation itself.